X-ray emission processes in stars and their immediate environment - Testa, Paola (National Academy of Sciences, 2010)
A decade of X-ray stellar observations with Chandra and XMM-Newton has led to significant advances in our understanding of the physical processes at work in hot (magnetized) plasmas in stars and their immediate environment, providing new perspectives and challenges, and in turn the need for improved models. The wealth of high-quality stellar spectra has allowed us to investigate, in detail, the characteristics of the X-ray emission across the Hertzsprung-Russell (HR) diagram. Progress has been made in addressing issues ranging from classical stellar activity in stars with solar-like dynamos (such as flares, activity cycles, spatial and thermal structuring of the X-ray emitting plasma, and evolution of X-ray activity with age), to X-ray generating processes (e.g., accretion, jets, magnetically confined winds) that were poorly understood in the preChandra/XMM-Newton era. I will discuss the progress made in the study of high energy stellar physics and its impact in a wider astrophysical context, focusing on the role of spectral diagnostics now accessible.